Financial and Operational Non-Disclosure and Corporate Tax Compliance in Nigeria: Evidence from the Telecommunications Sector - Oladipo Lawrence Babajide (Britain International for Academic Research (BIAR) Publisher, 2026)
The telecommunications sector plays a pivotal role in Nigeria’s digital economy and constitutes a major contributor to government revenue. However, increasing concerns have emerged regarding financial and operational non-disclosure practices within the sector and their implications for corporate tax compliance. This study investigates the intersection between non-disclosure practices and corporate tax compliance in Nigeria’s telecommunications industry. Anchored on corporate governance and regulatory compliance theory, the study examines how financial non-disclosure (such as underreported revenues and undocumented related-party transactions) and operational non-disclosure (including unreported data breaches and undisclosed network expansions) affect tax assessment accuracy, audit effectiveness, and compliance outcomes. Using a mixed-methods approach covering the period 2020–2025, the study analyzes regulatory frameworks, audit records, and stakeholder perceptions. The findings are expected to provide policy-relevant insights for harmonizing data protection obligations with tax transparency requirements, thereby strengthening fiscal accountability in Nigeria’s digital economy.